Analysis of Dropout Rates in Primary Schools in North Luwu Regency - Nursalim Nursalim (Edumaspul: Jurnal Pendidikan, 2023)
The issue of high dropout rates, particularly in compulsory education or basic education, requires effective suppression and reduction. This study aims to examine the dropout rate trends in primary and junior high schools within North Luwu Regency, located in the South Sulawesi Province. The data for this study was collected through a literature review and analyzed using descriptive statistics. Additionally, a regression test was conducted to analyze the trends. The research findings and data analysis indicate a declining trend in dropout rates for elementary and junior high school students, as represented by the equation Y = 176.429 - 23.429X. This downward trend signifies a positive direction for basic education in North Luwu.